Target size guidelines for interactive displays on the flight deck - Avsar, Huseyin; Fischer, Joel E.; Rodden, Tom (2015)
The avionics industry is seeking to understand the challenges and benefits of touchscreens on flight decks. This paper presents an investigation of interactive displays on the flight deck focusing on the impact of target size, placement and vibration on performance. A study was undertaken with search and rescue (SAR) crew members in an operational setting in helicopters. Results are essential to understand how to design effective touchscreen interfaces for the flight deck. Results show that device placement, vibration and target size have significant effects on targeting accuracy. However, increasing target size eliminates the negative effects of placement and vibration in most cases. The findings suggest that 15 mm targets are sufficiently large for non-safety critical Electronic Flight Bag (EFB) applications. For interaction with fixed displays where pilots have to extend their arms, and for safety critical tasks it is recommended to use interactive elements of about 20 mm size.